2020
DOI: 10.3389/fcell.2020.00218
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal on the Value of Using Nutraceutical Based Senolytics and Senostatics in Aging

Abstract: The average human life expectancy has increased globally, and continues to rise, owing to the substantive progress made in healthcare, medicine, sanitation, housing and education. This ultimately enriches society with a greater proportion of elderly people. Sustaining a healthy aged population is key to diminish the societal and economic impact of age-related infirmities. This is especially challenging because tissue function, and thus wellbeing, naturally progressively decline as humans age. With age increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Since several studies reported that synthetic senolytic chemical show side effect such as toxicity to normal cell despite the low effective concentration, the demand for natural substances that can offer similar effectiveness with fewer side effects is increasing [ 49 ]. Plant-derived compounds such as olive polyphenols, green tea catechins, resveratrol, fisetin has been reported to exert senolytic or senomorphic activity [ 50 ]. The effective concentration of these active compounds is less than 10 μg/mL while that of SMFE is 100–200 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Since several studies reported that synthetic senolytic chemical show side effect such as toxicity to normal cell despite the low effective concentration, the demand for natural substances that can offer similar effectiveness with fewer side effects is increasing [ 49 ]. Plant-derived compounds such as olive polyphenols, green tea catechins, resveratrol, fisetin has been reported to exert senolytic or senomorphic activity [ 50 ]. The effective concentration of these active compounds is less than 10 μg/mL while that of SMFE is 100–200 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of redox homeostasis due to prolonged exposure to oxidative stress (OS), manifested as reactive oxygen species (ROS)-mediated damage to biomolecules, has been identified as a crucial mediator for the progression of CS [ 5 9 ]. Although selective elimination of senescent cells (via senolytics) and prevention/slowed progression of senescence features (via senostatics) are attractive strategies, they also have undesirable adverse-effects such as high toxicity, low bioavailability, and chemical instability [ 10 12 ]. Therefore, the roles of biomolecules in maintenance of physiological homeostasis between OS and CS may provide novel strategies to promote healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, as these cells are important to normal homeostasis and physiology (99,101), their destruction comes at a fair cost. To illustrate the latter, the use of senolytics has been associated with reactivation of latent viral infections (242), systemic toxicity (243) and aberrant wound healing (244). Formal studies and clinical trials to assess their clinical efficacy are required prior to their consideration as therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%